(untitled) (Research, Society and Development, 2024)
Objective: To analyze the perceptions of healthcare professionals working in adult ICU regarding open visiting in light of the National Policy on Humanization (PNH) of the SUS. Methodology: A qualitative, exploratory, and descriptive study, operationalized through snowball sampling and semi-structured interviews, as described by Minayo. Thirteen healthcare professionals working in adult ICU in a municipality in Bahia were interviewed. Results and Discussion: Analysis of the professionals’ perceptions revealed significant issues on the topic, such as the professionals’ views on the presence of family in the ICU, the role of family in patient treatment, limits to implementing the ICU proposal, and the team-family relationship. Final Considerations: It was observed that knowledge and understanding of the PNH proposal are still distant from the reality of professional practice in ICU. Part of this is due to barriers such as lack of hospital infrastructure, which contributes to the maintenance of entrenched health care practices, among other factors. Therefore, there is a need to change health production processes to align with the concepts of expanded clinic and PNH’s environment, promoting the deconstruction of verticalities in work processes and generating greater user autonomy and social control within the SUS.